Chapter 10 School writing in Norway Fifteen years with writing as key competence - Skar, Gustaf Bernhard (Taylor & Francis, 2021)
Some 15 years ago, all teachers in Norway became writing teachers-at least according to the new curriculum-overnight. Following a "PISA-shock" in the early 2000s, Norwegian legislators decided to reform the national curriculum by introducing five cross-curricular "key competencies" to be taught by all teachers: writing, reading, mathematics, ICT and oracy. To accommodate teachers other than language arts teachers, the curriculum was amended to include subject-specific writing characteristics. This purpose of this chapter is twofold. First, an overview description of writing instruction in Norwegian schools using official documents as the main source is provided. Second, aided by a newly developed writing competency model, a fine-grained review of the language arts subject syllabi, the chapter presents an analysis of how writing and writing development is framed in the language arts subject syllabi.